Cacao Bean Polyphenols Inhibit Cardiac Hypertrophy and Systolic Dysfunction in Pressure Overload-induced Heart Failure Model Mice - Sari, Nurmila; Katanasaka, Yasufumi; Honda, Hiroki; Miyazaki, Yusuke; Sunagawa, Yoichi; Funamoto, Masafumi; Shimizu, Kana; Shimizu, Satoshi; Wada, Hiromichi; Hasegawa, Koji; Morimoto, Tatsuya (Planta Medica, 2020)
Pathological stresses such as pressure overload and myocardial infarction induce cardiac hypertrophy, which increases the risk of heart failure. Cacao bean polyphenols have recently gained considerable attention for their beneficial effects on cardiovascular diseases. This study investigated the effect of cacao bean polyphenols on the development of cardiac hypertrophy and heart failure. Cardiomyocytes from neonatal rats were pre-treated with cacao bean polyphenols and then stimulated with 30 µM phenylephrine. C57BL/6j male mice were subjected to sham or transverse aortic constriction surgery and then orally administered with vehicle or cacao bean polyphenols. Cardiac hypertrophy and function were examined by echocardiography. In cardiomyocytes, cacao bean polyphenols significantly suppressed phenylephrine-induced cardiomyocyte hypertrophy and hypertrophic gene transcription. Extracellular signal-regulated kinase 1/2 and GATA binding protein 4 phosphorylation induced by phenylephrine was inhibited by cacao bean polyphenols treatment in the cardiomyocytes. Cacao bean polyphenols treatment at 1200 mg/kg significantly ameliorated left ventricular posterior wall thickness, fractional shortening, hypertrophic gene transcription, cardiac hypertrophy, cardiac fibrosis, and extracellular signal-regulated kinase 1/2 phosphorylation induced by pressure overload. In conclusion, these findings suggest that cacao bean polyphenols prevent pressure overload-induced cardiac hypertrophy and systolic dysfunction by inhibiting the extracellular signal-regulated kinase 1/2-GATA binding protein 4 pathway in cardiomyocytes. Thus, cacao bean polyphenols may be useful for heart failure therapy in humans.
Keywords: cacao bean polyphenols; cardiac hypertrophy; heart failure; ERK1/2